4-8 yaş arası pes planovalguslu çocuklarda tabanlık uygulamasının ayak yük dağılımı ve fonksiyonel kapasiteye etkisi - Özgöncü, Nigar (Hasan Kalyoncu Üniversitesi, 2021)
Bu çalışma, 4-8 yaş arası pes planovalguslu (PPV) çocuklarda tabanlık uygulamasının ayak yük dağılımı ve fonksiyonel kapasiteye etkisini araştırmak amacıyla yapıldı. Çalışmamızda PPV'li 27 çocuk tedavi grubunu, 26 normal (sağlıklı) çocuk ise kontrol grubunu oluşturdu. Demografik bilgilerin kaydedilmesinin ardından yaşam kalitelerinin ölçümü için hem çocuklara hem de ebeveynlerine Oxford Ayak-Ayak bileği Anketi (OxAFQ) uygulandı. Değerlendirmelere tüm çocuklara navikular yükseklik (NY) ölçümü ve subtalar açı ölçümü yapılarak başlandı. Ayak yük dağılımını değerlendirmek için yürüme analiz cihazı ile hem tedavi hemde kontrol grubunun ayaklarının ölçümleri alındı. Fonksiyonel kapasite için her iki gruba da 2 Dakika Yürüme Testi (2-DYT) uygulandı. Tabanlık üretiminin ardından tedavi grubuna tabanlıkla statik ölçümler ve 2-DYT tekrarlandı. 3 aylık tabanlık kullanım sonrası kontrol için randevu verildi. Kontrole gelen çocuklara yapılan bütün değerlendirmeler tekrar uygulandı. Tabanlık kullanımının NY üzerinde olumlu etkisi bulunmazken (p>0.05), valgus açılarının iyileşmesine etkisi olduğu bulundu (p<0.05). Yük dağılımında anlık değerlendirmede ön-arka yük dağılımlarında kontrol grubu verilerinden farklı olarak eşit dağılım görüldü. Üç aylık tabanlık tedavisi sonucunda fark görülmedi (p>0.05). Tabanlık kullanımının fonksiyonel kapasitede 3 ay içerinde yürünen mesafe miktarını artırarak iyileşmeye etkisi olduğu saptandı (p<0.05). OxAFQ Anketi ile değerlendirilen yaşam kalitesinin fiziksel ve oyun skorlarının arttığı duygusal skorun azaldığı belirlendi (p<0.05). Tabanlık uygulamasının PPV'li çocuklarda valgus açısında iyileşme, ayak yük dağılımında simetri ve fonksiyonel kapasitede gelişme yarattığı gözlendi. Tabanlıklı ve tabanlıksız dinamik ölçümlerin yapılabildiği çalışmaların yararlı olacağı görüşündeyiz.

This study was conducted to investigate the effect of insoles on foot load distribution and functional capacity in children with pes planovalgus (PPV) aged 4-8 years. In our study, 27 children with PPV constituted the treatment group and 26 normal (healthy) children constituted the control group. After recording demographic information, the Oxford Foot-Ankle Questionnaire (OxAFQ) was administered to both children and their parents to measure their quality of life. Evaluations were started by measuring navicular height (NY) and subtalar angle for all children. In order to evaluate the foot load distribution, the measurements of the feet of both the treatment and control groups were taken with a gait analyzer. For functional capacity, 2-Minute Walking Test (2-MWT) was applied to both groups. After insole production, static measurements with insoles and 2-MWT were repeated in the treatment group. An appointment was made for control after 3 months of insoles use. All the evaluations made on the children who came to the control were applied again. While the use of insoles did not have a positive effect on NY (p>0.05), it was found to have an effect on the improvement of valgus angles (p<0.05). In the instantaneous evaluation of the load distribution, an equal distribution was observed in the front-rear load distributions, different from the control group data. There was no difference after three months of insoles treatment (p>0.05). It was determined that the use of insoles had an effect on improvement in functional capacity by increasing the amount of distance walked in 3 months (p<0.05). It was determined that the physical and game scores of the quality of life evaluated with the OxAFQ Questionnaire increased and the emotional score decreased (p<0.05). It was observed that the application of insoles resulted in improvement in valgus angle, symmetry in foot load distribution and improvement in functional capacity in children with PPV. We think that studies in which dynamic measurements with and without insoles will be useful.
The effect of insoles application on foot load distribution andfunctional capacity in children between 4 and 8 years with pes planovalgus
Keywords: Fizyoterapi ve Rehabilitasyon; Physiotherapy and Rehabilitation